LMO7 deficiency reveals the significance of the cuticular plate for hearing function - Ting-Ting Du (Nature Portfolio, 2019)
In contrast to the extensively studied mechanosensory hair bundle, the cuticular plate is not as well understood. In this study, authors describe the discovery of a hair cell protein called LIM only protein 7, which is localized in the cuticular plate and the cell junction and may play a role in age-related deafness.